The social impact of fantastic stories on teaching reading in the 5th year of Elementary School. (REMUNOM, 2025)
This study analyzes the use of the literary genre of fantasy in primaryeducation, focusing on its application in 5th grade classrooms. It investigates howteachers work with fantasy stories and their impacts on encouraging reading, as wellas the social and critical development of students. Based on a quantitative approach,questionnaires were applied to teachers to identify pedagogical practices andperceptions about the benefits of the genre. Fantasy, by stimulating imagination andcritical thinking, enhances engagement with reading and the development ofinterpretative skills. The study advocates for the inclusion of this genre in the schoolcurriculum as a tool for fostering more meaningful learning and contributing todiscussions on innovative pedagogical strategies in literature.